(untitled) (Journal of Engineering Science, 2020)
Trichloroethylene, and Benzene etc. in different landfill components such as landfill gas (LFG), leachate and waste due to emission from a selected waste disposal site at old Rajbandh, Khulna, Bangladesh. Level III Fugacity model was implemented on the selected evaluative environment and Monte Carlo simulation was used to account the variability and uncertainty of the model inputs as well as to observe its effect on the model outputs. It was found that Trichloroethylene had the highest concentration in waste compartment with a magnitude of 2.0E-02 mol/m3 and most of the mass (52%) was accumulated in waste compartment. It was found that m-Xylene was the highly persistent organic contaminant as it spends the highest amount of time in the modelled landfill environment. Reaction was the main removal mechanism for Trichloroethylene as about 79% of the total amount was removed by oxidation and hydrolysis reaction. It is essential to know the behaviour of potential harmful contaminants for assessing human health hazards from landfill site. The outcome of level III Fugacity model like mass, concentrations, etc. of organic contaminants generated from a selected landfill will further be helpful for evaluating health hazards from landfill site at Khulna. Journal of Engineering Science 11(1), 2020, 67-82